Grundtvig og Oxforderne - Allchin, Arthur M. (Grundtvig-studier, 1995)
Grundtvig and the oxfords Helge Grell: Grundtvig and the Oxfords. Grundtvigs meeting with the Oxford movement and its meaning for his authorship. Center for Grundtvig-studier, Aarhus Universitetsforlag 1995. 132 s. Kr. 178.By A. M. Allchin